Application of Real Option Valuation to Real Estate Investment Appraisal-- A Case Study - Lu, Yisha (2007)
This dissertation provides an insight of real option valuation application into real estate investment appraisal. Real estates investments have the features of low liquidity, slow payback and high sunk costs. This is especially the case appearing in emerging economics, due to the volatile demand, house price and land costs. The application of real options theory in real estate investment analysis considers a real estate development as an investment opportunity that reduces the uncertainties in the real estate development and creates economic value on real estate projects. A case study of a Chinese real estate development project "Jiangnan New Village" is conducted to illustrate the application of real option valuation to real estate investment appraisal in emerging real estate market. Binomial Tree approach is employed for real option valuation in the case study. The results lead to the conclusion that real options embedded in the real estate projects do create significant economic values on underlying project, and improve risk management of the project.